Evaluation of selenoproteins and proinflammatory cytokines in L-thyroxine-induced hyperthyroid rats: effects of selenium supplementation - Aysun Yoldas; Nurten Bahtiyar; Birsen Aydemir; Selmin Toplan (Archives of Endocrinology and Metabolism)
ABSTRACT Objective: This study investigated the effects of selenium, which is known for its antioxidant and immune-supporting properties, on serum levels of thyroid function markers, selenoproteins, and proinflammatory cytokines in a model of hyperthyroidism. Materials and methods: A total of 48 Wistar albino rats were distributed into 6 groups: a control group; a hyperthyroid group (HT group); a group fed 0.5 mg/kg sodium selenite (Se 1 group); a group fed 1 mg/kg sodium selenite (Se 2 group); a hyperthyroid group fed 0.5 mg/kg sodium selenite (HT + Se 1 group); and a hyperthyroid group fed 1 mg/kg sodium selenite (HT + Se 2 group) added to standard fodder. Serum levels of interleukin (IL)-1β, IL-6, IL-18, tumour necrosis factor alpha (TNF-α), selenoprotein P (SelP), and glutathione peroxidase 1 (GPx1) were measured using ELISAs. Results: IL-Iβ, IL-6, IL-18, and TNF-α levels were increased, but selenium, GPx1, and SelP levels were decreased in the hyperthyroid group compared with those in the control group. Selenium and GPx1 levels were increased, but TNF-α levels were decreased in the HT + Se 1 group compared with those in the HT group. Selenium, SelP, and GPx1 levels were increased, but TNF-α, IL-6, and IL-18 levels were decreased in the HT + Se 2 group compared with those in the HT group. Conclusion: Our results suggest that appropriate doses of selenium may be effective at preventing inflammation and providing protection against oxidative stress in hyperthyroid rats.